2009
DOI: 10.1038/bmt.2009.165
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of autologous PBSCT for peripheral T-cell lymphoma: retrospective analysis of the experience of the Fukuoka BMT group

Abstract: Peripheral T-cell lymphoma (PTCL) is generally characterized by poor prognosis after conventional chemotherapy compared with aggressive B-cell lymphoma. To elucidate the role of high-dose chemotherapy (HDCT) with auto-SCT, we retrospectively analyzed the outcomes of 39 patients with PTCL who received HDCT and auto-SCT between 1990 and 2005. Eleven patients were histologically typed as angioimmunoblastic, nine as anaplastic large-cell lymphoma, seven as natural killer/T-cell lymphoma and twelve as PTCL unspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…The prognosis for patients with PTCL, except for anaplastic lymphoma kinase (ALK)-positive, anaplastic large cell lymphoma (ALCL), is poor. Therefore, several groups reported adding consolidation treatment for patients in CR1 with HDT and ASCT (12)(13)(14)(15). These reports showed CR at ASCT was a significant prognostic factor for event-free survival (EFS) and OS and suggested that HDT and ASCT may be effective as consolidation in CR for PTCL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for patients with PTCL, except for anaplastic lymphoma kinase (ALK)-positive, anaplastic large cell lymphoma (ALCL), is poor. Therefore, several groups reported adding consolidation treatment for patients in CR1 with HDT and ASCT (12)(13)(14)(15). These reports showed CR at ASCT was a significant prognostic factor for event-free survival (EFS) and OS and suggested that HDT and ASCT may be effective as consolidation in CR for PTCL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notable exceptions were patients with anaplastic lymphoma kinase (ALK) mutated anaplastic large cell lymphoma (ALCL), as these patients have favorable outcomes with anthracycline-containing chemotherapy alone, and patients with IPI high-risk or high-risk PIT scores at presentation, as these patients as a whole have not yet shown significant benefit from frontline, consolidative ASCT, albeit in subgroup analyses [Laport, 2010]. In Table 5, six of these trials involving 452 patients are summarized [Corradini et al 2006;Feyler et al 2007;Rodriguez et al 2007aRodriguez et al , 2007bMercadal et al 2008;Reimer et al 2009;Numata et al 2010].…”
Section: Consolidative Asct For Patients With Ptcl Following Inductionmentioning
confidence: 99%
“…5 On the other hand, the outcomes were equivalent in patients treated with high-dose sequential chemotherapy followed by autologous transplantation (ASCT). [25][26][27][28][29][30] It has been reported that there is marked variability in the 5-year relative survival rate across PTCL subtypes, and that there has been no clear improvement in survival among PTCL patients over time. 31 This finding is in sharp contrast to the improvement in OS seen for B-cell NHLs over the same time period, [18][19][20][21] which is due mainly to advances in therapy, particularly the addition of immunotherapy using anti-CD20 rituximab.…”
Section: Figmentioning
confidence: 99%